PENGARUH FAKTOR FUNDAMENTAL DAN RISIKO SAHAM TERHADAP HARGA SAHAM DI BURSA EFEK INDONESIA (BEI) - Citrawati Jatiningrum (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2012)
This research aims to prove empirically the influence of fundamental factors (NPM, EPS,ROA, ROE, DPR, DER, PBV) and total risk of stock of either through parsial and also simultan tostock price at manufacturing business which go public in Indonesia Stock Exchange. Technique ofIntake sampel use the method of purposive sampling, is so that obtained by sampel as much 10manufacturing business enlisted in BEI period 2006-2009. Hypothesis test done by using linearanalysis regresi model and multiple linear regresi. Result of this research indicate that by parsial isNPM (net profit margin), EPS (earning per share), ROA (return on asset), and PBV (price to bookvalue) having an effect on signifikan to stock price, while ROE (return on equity), DPR (dividendpayout ratio), DER (debt to equity ratio), and total risk of company stock do not have an effect on thesignifikan to stock price. But by simultan is fundamental factor (NPM, EPS, ROA, ROE, DPR, DER,PBV) and total risk of stock have an effect on the signifikan to stock price at manufacturing businesswhich go public in Indonesia Stock Exchange (BEI). Result of test by parsial indicate that do not allindependent variable have an effect on to stock price, meaning that stock price do not mirror allexisting information, this matter because of capital market in Indonesia still the in form of weak go tostrong semi, and also stock price also can be influenced by factors of outside this research liketechnical factor and or economic factor. By parsial result of this research is consistent with theresearch of Krisantini Putri (2008), while by simultan result of this research is consistent with theprevious research done by Anastasia et al. (2003).